Why gastric perforation occurs in patients with isolated esophageal atresia: more vulnerable stomach? - Acer, Tuğba; Karnak, İbrahim and Yalçın, Şule and Şenocak, Mehmet Emin (The Turkish Journal of Pediatrics, 2012)
Gastric perforation (GP) in patients with isolated esophageal atresia (EA) is seen more than expected. The etiology of the perforation may be vulnerability of these immature stomachs. Gastrostomy operation should be performed by gentle handling. The volume of gastrostomy feedings should be increased incrementally. The early diagnosis of perforation is only possible with a high index of suspicion. The stomach should be visualized by gastrography with soluble contrast material as soon as the perforation is suspected.